2015
DOI: 10.1055/s-0035-1563537
|View full text |Cite
|
Sign up to set email alerts
|

Freezing Equals Freezing? Performance of Two Cryoablation Devices in Concomitant Mitral Valve Repair

Abstract: Recent guidelines have recommended the addition of ablation in cardiac surgery for patients presenting with atrial fibrillation (AF). Currently available cryoablation devices use either nitrous oxide or argon gas as cooling agent. Our study aimed to compare success rates of two different devices currently available on the market and applied during concomitant cardiac surgery. Between 2009 and 2012, data were collected from 120 consecutive patients in whom either the aluminum cryoICE ablation probe (AtriCure, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…However, does the efficacy of a colder cryoprobe change the rhythm outcomes? An observational study, with all its biases, reported better rhythm outcomes for the nitrous oxide probe compared to the argon one ( 46 ). In contrast, a recent randomized controlled trial showed no significant difference between the two probes at 1- ( 47 ) and 5-year ( 48 ) follow-up.…”
Section: Energy Sourcesmentioning
confidence: 99%
“…However, does the efficacy of a colder cryoprobe change the rhythm outcomes? An observational study, with all its biases, reported better rhythm outcomes for the nitrous oxide probe compared to the argon one ( 46 ). In contrast, a recent randomized controlled trial showed no significant difference between the two probes at 1- ( 47 ) and 5-year ( 48 ) follow-up.…”
Section: Energy Sourcesmentioning
confidence: 99%
“…Therefore, high thermal conductivity of the material chosen for an applicator plays significant role. Due to this, common applicators are made of metals [38][39][40][41]. At the same time, sapphire features high thermal conductivity at cryogenic temperatures, that along with the mentioned properties makes it a favorable material for cryosurgery [42].…”
Section: Introductionmentioning
confidence: 99%